Molecular neuropathology of the synapse in sheep with CLN5 Batten disease. Issue 11 (9th October 2015) - Amorim, Inês S.; Mitchell, Nadia L.; Palmer, David N.; Sawiak, Stephen J.; Mason, Roger; Wishart, Thomas M.; Gillingwater, Thomas H.
Abstract: Aims: Synapses represent a major pathological target across a broad range of neurodegenerative conditions. Recent studies addressing molecular mechanisms regulating synaptic vulnerability and degeneration have relied heavily on invertebrate and mouse models. Whether similar molecular neuropathological changes underpin synaptic breakdown in large animal models and in human patients with neurodegenerative disease remains unclear. We therefore investigated whether molecular regulators of synaptic pathophysiology, previously identified in Drosophila and mouse models, are similarly present and modified in the brain of sheep with CLN5 Batten disease. Methods: Gross neuropathological analysis of CLN5 Batten disease sheep and controls was used alongside postmortem MRI imaging to identify affected brain regions. Synaptosome preparations were then generated and quantitative fluorescent Western blotting used to determine and compare levels of synaptic proteins. Results: The cortex was particularly affected by regional neurodegeneration and synaptic loss in CLN5 sheep, whilst the cerebellum was relatively spared. Quantitative assessment of the protein content of synaptosome preparations revealed significant changes in levels of seven out of eight synaptic neurodegeneration proteins investigated in the motor cortex, but not cerebellum, of CLN5 sheep ( α ‐synuclein, CSP‐ α, neurofascin, ROCK2, calretinin, SIRT2, and UBR4). Conclusions: Synaptic pathology is a robust correlate of region‐specific neurodegeneration in the brain of CLN5 sheep, driven by molecular pathways similar to those reported in Drosophila and rodent models. Thus, large animal models, such as sheep, represent ideal translational systems to develop and test therapeutics aimed at delaying or halting synaptic pathology for a range of human neurodegenerative conditions. Abstract : Synaptic degeneration is a major feature of many neurodegenerative diseases, with the underlying molecular mechanisms starting to be uncovered in a range of small animal models. Here, we provide comparable evidence for synaptic pathology in sheep with Batten disease and reveal molecular changes in degenerating synapses remarkably consistent with those regulating synaptic pathology in mouse and Drosophila models.